Application of TOPSIS analysis method in financial performance evaluation: a case study of construction sector in Malaysia / Zati Halwani Abd Rahim … [et al.] - Abd Rahim, Zati Halwani; Azhar, Farah Waheeda; Abdullah Fahami, Norasyikin; Abd Karim, Hilwana; Nor Abdul Rahim, Siti Khatijah (Universiti Teknologi Mara Selangor, 2020)
This research aims to propose TOPSIS model in evaluating, comparing, and ranking the Malaysian companies under the construction sector according to their financial performance using financial ratio. Previously, TOPSIS model and financial ratio as tools of measurement have been applied to evaluate, compare, and rank the financial performance of the companies. Nevertheless, there are not many researches have been done on TOPSIS model in Malaysia’s construction sector. Hence, this paper intends to fill in the loopholes by assessing the performance of the companies from the construction sector in Malaysia stock market by implementing the proposed model. Based from the findings, TOPSIS model was able to assess the companies’ financial performance and consequently rank them. The results from the study parallel with the study done by other investment agencies. Therefore, this method can be opted to substitute the fundamental and technical valuation that is commonly utilised by the investment analysts.